NLRP6 Inflammasome Orchestrates the Colonic Host-Microbial Interface by Regulating Goblet Cell Mucus Secretion - Wlodarska, Marta; Thaiss, Christoph A.; Nowarski, Roni; Henao-Mejia, Jorge; Zhang, Jian-Ping; Brown, Eric M.; Frankel, Gad; Levy, Maayan; Katz, Meirav N.; Philbrick, William M.; Elinav, Eran; Finlay, B. Brett; et al. (Cell, 2014)
Mucus production by goblet cells of the large intestine serves as a crucial antimicrobial protective mechanism at the interface between the eukaryotic and prokaryotic cells of the mammalian intestinal ecosystem. However, the regulatory pathways involved in goblet cell-induced mucus secretion remain largely unknown. Here, we demonstrate that the NLRP6 inflammasome, a recently described regulator of colonic microbiota composition and biogeographical distribution, is a critical orchestrator of goblet cell mucin granule exocytosis. NLRP6 deficiency leads to defective autophagy in goblet cells and abrogated mucus secretion into the large intestinal lumen. Consequently, NLRP6 inflammasome-deficient mice are unable to clear enteric pathogens from the mucosal surface, rendering them highly susceptible to persistent infection. This study identifies an innate immune regulatory pathway governing goblet cell mucus secretion, linking nonhematopoietic inflammasome signaling to autophagy and highlighting the goblet cell as a critical innate immune player in the control of intestinal host-microbial mutualism. [Display omitted] [Display omitted] •The NLRP6 inflammasome is highly expressed in intestinal goblet cells•NLRP6 inflammasome regulates goblet cell mucus secretion•NLRP6 regulation of goblet cells is mediated through induction of autophagy•Altered NLRP6 signaling induces impaired mucus layer and susceptibility to infection Intestinal goblet cells secrete mucus and antimicrobial peptides to ward off pathogens, with the NLRP6 inflammasome, an immune sensor, being central to regulating mucus granule secretion.